2016
DOI: 10.1016/j.trecan.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms of Regulation of miRNAs in CLL

Abstract: B-cell chronic lymphocytic leukemia (CLL) is the most common adult human leukemia. Although, the molecular alterations leading to CLL onset and progression are still under investigation (specifically, the interplay and exact role of oncogenes and tumor suppressors in CLL pathogenesis). MicroRNAs are small non-coding RNAs that regulate gene expression and are expressed in a tissue specific manner. Deregulation of microRNAs can alter expression levels of genes involved in the development and/or progression of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 71 publications
(117 reference statements)
0
32
0
Order By: Relevance
“…Bonci et al (2008) showed that CCND1 and WNT3A are targets of this cluster and forced expression induced growth arrest and apoptosis. Anti-apoptotic genes (BCL-2, Activin A and CCND1) (Bonci et al, 2008;Li et al, 2013a;Bufalino et al, 2015) and pro-apoptotic genes (p53, BIM and Caspase-7) (Tang et al, 2013;Balatti et al, 2016;Robaina et al, 2016) are often targets of miRNA clusters and are important for inhibiting apoptosis. miR-106b/25 is significantly upregulated in prostate cancer and shows resistance to apoptosis by targeting CASP7 (Hudson et al, 2013).…”
Section: (4) Cell Cycle Progressionmentioning
confidence: 99%
“…Bonci et al (2008) showed that CCND1 and WNT3A are targets of this cluster and forced expression induced growth arrest and apoptosis. Anti-apoptotic genes (BCL-2, Activin A and CCND1) (Bonci et al, 2008;Li et al, 2013a;Bufalino et al, 2015) and pro-apoptotic genes (p53, BIM and Caspase-7) (Tang et al, 2013;Balatti et al, 2016;Robaina et al, 2016) are often targets of miRNA clusters and are important for inhibiting apoptosis. miR-106b/25 is significantly upregulated in prostate cancer and shows resistance to apoptosis by targeting CASP7 (Hudson et al, 2013).…”
Section: (4) Cell Cycle Progressionmentioning
confidence: 99%
“…≤ 0.05) were analyzed with DASHR and UCSC human genome browser for sequence annotations. Five of the novel miRs (novelmiR_4291, novelmiR_1520, novelmiR_1559, novelmiR_1732 and novelmiR_4370) showed homology with a multitude of tRNA molecules located on chromosomes 1,6,7,9,11,12,14,15,16, and 17 (supplementary table 1). The novelmiR_4370 showed homology with a piRNA-36225 (alias piRNA-28374; GenBank: DQ598159.1) as well.…”
Section: Annotation Of Novel Mirsmentioning
confidence: 99%
“…In the landmark study of Calin et al, a 13 miR signature was reported in CLL patients with high Zeta-chain-associated protein kinase 70 (ZAP70) expression and unmutated immunoglobulin heavy chain variable region gene (IGHV) status 6 . Differential expression of various miRNAs including miR-15a, miR-16, miR-29a/b/c, miR-223 and miR-150 have been consistently reported to be associated with well established prognostic factors such as IGHV status, ZAP70/ CD38 expression, β2 microglobulin levels and disease progression in CLL 11 . A few studies have identified karyotype specific miR signatures in CLL that could discriminate patients harboring del(17p), del(11q), del(13q), trisomy 12, and normal karyotype 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…14 They mediate the deacetylation and demethylation of lysine residues (H3K9/14 and H3K4me3) on histones to silence genes, 15,16 and in CLL, they have been shown to silence the expression of key microRNA genes (miRNAs or miRs) and miRs such as miR-15a, miR-16, miR-29b, and miR-106b. 17,18 However, the role of miRs in targeting BTK, their expression levels in CLL, and the role of HDACs in dysregulating the BTK-targeting miRs are unknown.…”
Section: Introductionmentioning
confidence: 99%